Agent based simulation for pedestrian movement during panic situation - Mustafa, Masria; Abd Rahman, Zanariah; Bachok, Syahriah (2013)
Evacuation is the movement of people from a dangerous to a safer location. To minimize casualties during a panic situation, building design should consider evacuation plans. An evacuation process is complicated and interrupted by irregular behavior, pedestrians’ or agents’ characteristics, time limit and the surrounding environment. The computer simulation software SimWalk was used in this study to plan for an evacuation during a panic situation. It is revealed that when the bottleneck occurred, pedestrians would collide with each other, hence increasing the friction between them.